Analysis of Management Function Management in Financial Administration in Buton District - R, Muh. Rais.; Daholu, Ahmad (Institute for Research and Community Service, 2022)
The purpose of this research is to find out how to make the analysis of the financial administrative management function in the Siotapina District Office of Buton Regency run better and how to manage the financial administration there. The research approach is qualitative. The informants in this study were employees of the Siotaping District Office, Buton Regency, especially the Head of the Xiotapina District Office, the Finance Section or Treasurer, and related fields within it, which was carried out in August 2022. The data sources used were primary data sources and secondary data sources. While the data collection technique used is question and answer and documentation. The findings show that the Siotapina District Office of Buton Regency manages the financial administrative management function optimally, because 96% of the goals or budget are carried out in 2018 and 96% in 2019. and becomes 96% in 2020. Set at 95 percent. In addition, the procedure for managing the financial administration of the Siotapa District Office adheres to accrual state accounting rules, but is limited to a network system for the purposes of carrying out activities and reporting.